Historical Trajectories of Sino–Nusantara Relations - Ahmad Suaedy; Fariz Alnizar; Muhammad Hasan Basri; Idris Masudi (Faculty of Islam Nusantara, Nahdlatul Ulama University of Indonesia (Unusia) Jakarta., 2026)
This 2025 special issue of Islam Nusantara: Journal for the Study of Islamic History and Culture, collaboratively organized with the Cheng Ho Cultural Museum, presents a multidisciplinary exploration of the historical and contemporary dimensions of Sino-Nusantara relations. Through five thematic lenses, maritime routes, Islamization, artistic heritage, culinary history, and geopolitical dynamics, the featured articles employ diverse methodologies ranging from ethnography and historiography to international relations theory. Collectively, they challenge reductionist narratives by highlighting the integral role of Chinese Muslim communities, the hybridity of cultural expressions, and the enduring legacy of inter-civilizational encounters. The issue reframes Islam Nusantara as a product of layered, continuous negotiation, demonstrating how historical connectivity informs both cultural identity and modern geopolitical frameworks. Ultimately, it advocates for an adaptive, inclusive understanding of this shared past to envision more cooperative futures.